Influence of dental materials on dental MRI - Tymofiyeva, O (The British Institute of Radiology., 2013)
OBJECTIVES: To investigate the potential influence of standard dental materials on dental MRI (dMRI) by estimating the magnetic susceptibility with the help of the MRI-based geometric distortion method and to classify the materials from the standpoint of dMRI. METHODS: A series of standard dental materials was studied on a 1.5 T MRI system using spin echo and gradient echo pulse sequences and their magnetic susceptibility was estimated using the geometric method. Measurements on samples of dental materials were supported by in vivo examples obtained in dedicated dMRI procedures. RESULTS: The tested materials showed a range of distortion degrees. The following materials were classified as fully compatible materials that can be present even in the tooth of interest: the resin-based sealer AH Plus(®) (Dentsply, Maillefer, Germany), glass ionomer cement, gutta-percha, zirconium dioxide and composites from one of the tested manufacturers. Interestingly, composites provided by the other manufacturer caused relatively strong distortions and were therefore classified as compatible I, along with amalgam, gold alloy, gold–ceramic crowns, titanium alloy and NiTi orthodontic wires. Materials, the magnetic susceptibility of which differed from that of water by more than 200 ppm, were classified as non-compatible materials that should not be present in the patient’s mouth for any dMRI applications. They included stainless steel orthodontic appliances and CoCr. CONCLUSIONS: A classification of the materials that complies with the standard grouping of materials according to their magnetic susceptibility was proposed and adopted for the purposes of dMRI. The proposed classification can serve as a guideline in future dMRI research.